Pelatihan Pembuatan Hantaran Pengantin Pengisi Waktu Luang bagi Ibu PKK - Susilowati, Sri; Farida, Ilya (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
The aims of the Community Service is to empower the target audience to have knowledge about the importance of using leisure time with positive activities that can bring in additional income by making bridal delivery for a group of PKK women in Griya Permata Hijau Housing, Candi, Sidoarjo. Methods used for the implementation of Community Service activities are as follows: 1. Provision of materials with lecture and discussion or question and answer methods related to materials and equipment used for training the manufacture of bridal delivery, 2. Practice Method is used when the Tutor demonstrate bridal delivery process with Tutor guidance. Community service activities are expected to increase knowledge for a group of PKK mothers related to the problem of bridal bridge making skills, so later after following this activity have the knowledge and skills that can be utilized to fill the spare time with positive activities and can help to supplement family income through the utilization of delivery services for the needy. Increased knowledge and skills in addition to increase family income, is expected to also improve the welfare and quality of life for his family. Keywords: Bridal Bridges, Leisure Time, Sidoarjo’s women